Effect of saturation temperature and vapor quality on the boiling heat transfer and critical heat flux in a microchannel - Dalkilic, Ahmet Selim; Celen, Ali; Erdogan, Murat; Sakamatapan, Kittipong; Newaz, Kazi Salim; Wongwises, Somchai (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
In this paper, heat transfer coefficients and critical heat fluxes of the R134a fluid in two-phase flow was studied in a 27-channel, 421 mu m hydraulic diameter and 40 mm long microchannel experimental set-up. Data were collected at constant mass flux of 1000 kg m(-2) s(-1), saturation inlet temperature range of 20-28 degrees C and at inlet vapor quality range of 0.01-0.20. The heat flux was initiated at 250 kW m(-2) and gradually increased until reaching the critical heat flux (CHF). The effect of inlet vapor quality, saturation inlet temperature and heat flux on heat transfer coefficient and critical heat flux were investigated in detail and presented graphically. It can be observed that the CHF decreases with the increasing of saturation inlet temperature and inlet vapor quality. However, the heat transfer coefficient at the CHF point increased with the increasing of saturation temperature and the heat transfer coefficient at the CHF point was decreased with the increasing of vapor quality. The test results from the correlations, suggested in well-known articles, were compared with the experimental data, where the Kosaz et al. proposed correlation was showing well fit with the experimental data having absolute error of 9.86%. In this investigation, the new correlations for the heat transfer coefficient for the heat transfer coefficient and the critical heat flux have been proposed by taking into account the effect of the vapor quality.
Keywords: Boiling; CHF; Two phase flow; Criticical heat flux; Microchannel; R134a; PRESSURE-DROP; WATER-FLOW; TUBES; PREDICTION; SINGLE; CHANNEL; Thermodynamics; Mechanics